Analyzing Product Quality And Price On The Decision To Purchase Uniqlo Products - Indriasari, Dewi Pratiwi (Jurnal Economic Resource, 2024)
Leadership and knowledge management play a pivotal role in enhancing employee performance, particularly within service offices where efficiency, quality, and adaptability are paramount. Effective leadership fosters a collaborative and goal-oriented work environment, empowering employees through motivation, clear direction, and supportive communication. Meanwhile, knowledge management ensures the systematic acquisition, storage, sharing, and application of organizational knowledge, enabling employees to perform tasks efficiently and innovate effectively. This study examines the interplay between leadership styles and knowledge management practices in influencing employee performance within service offices. By analyzing qualitative and quantitative data from service organizations, the research identifies key leadership attributes—such as transformational and participative approaches—that align with robust knowledge-sharing cultures. The findings suggest that integrating adaptive leadership with strategic knowledge management not only improves individual and team performance but also enhances organizational agility and customer satisfaction. This paper provides actionable insights for leaders and managers in service offices, emphasizing the importance of fostering a learning-oriented culture and aligning leadership strategies with knowledge management practices to achieve optimal employee performance.